Penentuan Kondisi Optimum Adsorpsi Kromium (III) Menggunakan Biosorben dari Limbah Kulit Nangka (Artocapus heterophyllus) - Karina Ardiani; Arifah Nur Raya; Inayati Inayati (Program studi Teknik Kimia UNS, 2017)
The purposes of the research are determine the optimum condition and themaximum adsorpstion of Cr (III) by biosorben from jackfruit peel. The process of theadsorption was started by to put 0.03 grams jackfruit peel adsorben to Cr(NO3)3 solution2.5 ppm. The variables of the research are activation time, contact time between theadsorben and the solution, and pH of the solution. The sample was analyzed byAbsorption Spectrophotometre (AAS) to show the Cr (III) concentration on the solutions.The optimum condition was reached at 5 pH level with 50 minute of contact times and 24hours activation time. The analysis results that the adsorption follows Langmuir Isotermshowed by the determinant value (R2). The maximum power adsorption is 1.227 mg/gramadsorben